The Dynamical History of HIP-41378 f—Oblique Exorings Masquerading as a Puffy Planet - Tiger Lu; Gongjie Li; Ben Cassese; D. N. C. Lin (The Astrophysical Journal)
The super-puff HIP-41378 f represents a fascinating puzzle due to its anomalously low density on a far-out orbit in contrast with other known super-puffs. In this work, we explore the hypothesis that HIP-41378 f is not in fact a low-density planet, but rather hosts an opaque ring system. We analyze the dynamical history of the system and show that convergent migration is necessary to explain the system's long-term stability. We then show that this same migration process plausibly captures HIP-41378 f into spin–orbit resonance and excites the planetary obliquity to high values. This tilts the surrounding ring and is a plausible explanation for the large transit depth. In the end, we also briefly comment on the likelihood of other super-puff planets being in high-obliquity states. We show that the existence of a tilted extensive ring around a high obliquity planet can serve as an explanation for puffy planets, particularly in multiplanetary systems at far distances from their host stars.